Methotrexate Induced Pancytopenia - Fernando Gonzalez-Ibarra; Sahar Eivaz-Mohammadi; Shiri Surapaneni; Hazem Alsaadi; Amer K. Syed; Simon Badin; Valentin Marian; Mazhar Elamir (Case Reports in Rheumatology)
The well-reported methotrexate (MTX) toxicities are based on the duration and cumulative dosing of drug. The typical toxicities can be predicted by the timing of drug administration, where mucositis occurs as an earlier effect, while myelosuppression and the sequelae of pancytopenia occur later after MTX administration. Despite these well-known toxicities, low dose MTX therapy can become problematic, in particular with the elderly, who are at a greater risk for significant myelosuppression. We present a case of a 73-year-old female with pancytopenia causing severe neutropenia, mucocutaneous bleeding, and bruising and requiring intravenous antibiotic therapy and limited transfusion dependence as a result of low dose daily MTX for rheumatoid arthritis.